The Clinical and Pathological Characteristics of Refractory Pituitary Adenomas: A Single Center Experience - Liu, Xiaohai; Dai, Congxin; Bao, Xinjie; Deng, Kan; Yao, Yong; Feng, Ming; Li, Mingchu; Chen, Ge; Wang, Renzhi (Frontiers in Oncology, 2022)
Background: Most of pituitary adenomas (PAs) are slowly growing benign tumors which can be cured or controlled by conventional therapies, including surgery, medical treatment or radiotherapy. A small set of PAs, usually known as aggressive PAs or refractory PAs, present with more aggressive behavior and lead to poorer prognosis than classical PAs. However, there is no general agreement regarding the diagnostic criteria of refractory PA till now. Methods: We retrospectively analyzed the clinical and pathological characteristics of 44 patients who were diagnosed as refractory PAs by a multidisciplinary team (MDT). All the patients’ demographic characteristics, radiological findings, Knosp grade, treatment details and clinical outcome were abstracted from the medical record. Additionally, 44 patients with non-refractory PAs (NRPAs) matched for age and gender were selected to serve as control group. Results: Despite using all those combined treatments including surgery, radiotherapy and conventional medical treatments, all the refractory PAs showed tumor progression or hormone hypersecretion which caused increased morbidity and mortality and remain challenging to manage. Compared to the non-refractory PAs, the tumor size, invasive rate and tumor growth rate (TGA) were significantly higher in the refractory PAs. TGA >3% per month may be considered as a preoperative indicator of refractoriness. The Ki-67 index in the refractory PAs were all ≥2.2%. EGFR, but not MMP2 or MMP9 were significantly over-expressed in refractory PAs compared with the corresponding levels in non-refractory PAs. Conclusion: Refractory PAs are is unresponsive to surgery, radiotherapy and conventional medical treatments with a poor prognosis. Moreover, the tumor growth rate ≥2.2% per month, Ki-67 index and EGFR may be independent predictors of clinical refractoriness.